+0  
 
0
262
4
avatar

Fill in the appropriate operation signs ( +, -, × ,÷ ,√,) to make the following sentances true.

 

2 2 2 = 6                    6 6 6 = 6

3 3 3 = 6                    7 7 7 = 6

4 4 4 = 6                    8 8 8 = 6 

5 5 5= 6                     9 9 9= 6                                                                           GOOD LUCK 

Guest Jan 16, 2015

Best Answer 

 #1
avatar+81061 
+10

2 + 2 + 2 = 6                    (6 x 6 ) / 6 = 6

(3 x 3) - 3 = 6                    7 - (7 / 7) = 6

4 + 4 - √4 = 6                  8 - √ (√( 8 + 8))  =  8 - √√(16)   = 8 -√4 = 8 - 2  = 6

5 + (5 / 5)= 6                    (√ 9  x √9 )  - √9 = 6    

 

CPhill  Jan 16, 2015
Sort: 

4+0 Answers

 #1
avatar+81061 
+10
Best Answer

2 + 2 + 2 = 6                    (6 x 6 ) / 6 = 6

(3 x 3) - 3 = 6                    7 - (7 / 7) = 6

4 + 4 - √4 = 6                  8 - √ (√( 8 + 8))  =  8 - √√(16)   = 8 -√4 = 8 - 2  = 6

5 + (5 / 5)= 6                    (√ 9  x √9 )  - √9 = 6    

 

CPhill  Jan 16, 2015
 #2
avatar+91477 
+5

That looks like a fun little exercise. 

Melody  Jan 16, 2015
 #3
avatar+808 
+5

Alternatives:

 

2 * 2 + 2 = 6                         6/6 * 6 = 6

√3 * √3 + 3 = 6                     6√6 / √6 = 6

√(4 *4)+√4 = 6                     6/√6 *√6 = 6

4 * √4) - √4 = 6                    9 - (9 / √9) = 6

√√(4*4) + 4 = 6                    9 - √(√9 * √9) = 6

                                             9 - √√(9 * 9) = 6

Tetration  Jan 17, 2015
 #4
avatar+81061 
+5

Thanks for those alternatives, Tetration......these kinds of things are always fun to play around with......making 6 with three "8s"  was kind of hard to figure out......!!!!

 

CPhill  Jan 17, 2015

6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details